Chlorogenic acid potentiates antitumor effect of doxorubicin through upregulation of death receptors in solid Ehrlich carcinoma model in mice. Issue 1 (2nd January 2019) - Abd Elrazik, Nesma A.; El-Mesery, Mohamed; El-Karef, Amro; Eissa, Laila A.; El Gayar, Amal M
ABSTRACT: This study aimed to evaluate the antitumor effect of chlorogenic acid (CGA) alone and in combination with doxorubicin (DOX) in solid Ehrlich carcinoma (SEC) model in mice. In addition, we investigated the possible cardioprotective effect of CGA against DOX-induced cardiotoxicity. CGA, DOX and their combination were given for 21 days in mice bearing SEC. Tumor volume and weight were measured, and serum CRP was determined by latex immunoassay. Moreover, mRNA expressions of TRAIL, TRAILR2, FasL, Fas, caspase-3 and Bcl-2 were measured using RT-PCR. Histopathological examination of tumor and cardiac tissues was carried out using hematoxylin and eosin. Active caspase-3 was detected by immunohistochemistry. CGA and/or DOX treatment showed a remarkable decrease in solid tumor volume and weight. CGA and/or DOX groups revealed upregulation in gene expressions of TRAIL/TRAILR2, FasL/Fas and caspase-3 genes and downregulation of Bcl-2 gene expression, as well as a marked increase in active caspase-3 expression. Moreover, CGA and DOX combination significantly decreased MDA and increased GSH levels in tumor tissues and also reduced the level of serum CRP, CK-MB and LDH as compared to DOX group. In conclusion, CGA has the ability not only to enhance the anti-tumor activity of DOX but also protects against DOX-induced cardiotoxicity.